1993
DOI: 10.1177/10454411930040031401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Whole Saliva Components on Enamel Demineralization In Vitro

Abstract: The aim of the present study was to use an in vitro enamel demineralization model (1) to confirm that whole saliva pretreatment conferred acid resistance to dental enamel and (2) to determine whether this phenomenon was attributable to specific salivary proteins, minerals, lipids, or some combination of these. Crowns of human teeth, each with one exposed window, were prepared in groups of ten. They were each pretreated by immersion individually in 4 ml of either (1) clarified whole saliva for 18, 72, or 168 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 15 publications
4
31
0
4
Order By: Relevance
“…Estos cristales de hidroxiapatita son susceptibles a la acción de los ácidos constituyendo esta característica el sustrato químico que da origen a las caries y erosión dental (Mas). La desmineralización se produce cuando la acidez se sitúa por debajo del pH 5.5 que es el pH crítico de la hidroxiapatita, de esta forma se producirá una liberación de iones de calcio y fosfato desde el esmalte hacia el medio circundante (Featherstone et al, 1993) provocando erosión en las piezas dentarias, éste término deriva del latín erodere, erosi, erosum (corroer) el cual describe el proceso de destrucción gradual de la superficie de un cuerpo, generalmente por procesos electrolíticos o químicos (Liñan et al, 2007), no incluyendo la participación de microorganismos de la flora bacteriana intraoral (Narváez, 2008). En los últimos años ha existido un gran incremento en la prevalencia de la erosión dental, sobretodo en la población de niños y adolescentes, siendo uno de los factores de riesgo más importante la ingesta de bebidas carbonatadas (Liñan et al), bebidas ácidas, light, deportivas y jugos de frutas (Zero &Lussi).…”
Section: Introductionunclassified
“…Estos cristales de hidroxiapatita son susceptibles a la acción de los ácidos constituyendo esta característica el sustrato químico que da origen a las caries y erosión dental (Mas). La desmineralización se produce cuando la acidez se sitúa por debajo del pH 5.5 que es el pH crítico de la hidroxiapatita, de esta forma se producirá una liberación de iones de calcio y fosfato desde el esmalte hacia el medio circundante (Featherstone et al, 1993) provocando erosión en las piezas dentarias, éste término deriva del latín erodere, erosi, erosum (corroer) el cual describe el proceso de destrucción gradual de la superficie de un cuerpo, generalmente por procesos electrolíticos o químicos (Liñan et al, 2007), no incluyendo la participación de microorganismos de la flora bacteriana intraoral (Narváez, 2008). En los últimos años ha existido un gran incremento en la prevalencia de la erosión dental, sobretodo en la población de niños y adolescentes, siendo uno de los factores de riesgo más importante la ingesta de bebidas carbonatadas (Liñan et al), bebidas ácidas, light, deportivas y jugos de frutas (Zero &Lussi).…”
Section: Introductionunclassified
“…This adsorption is assumed to be dependent on the chemical characteristics of the surface as well as the properties of the particular proteins. The enamel pellicle evidently prevents demineralization of the surface hydroxyapatite, increasing its acid resistance, although the mechanisms responsible for this effect remain elusive (Zahradnik et al 1976(Zahradnik et al , 1977(Zahradnik et al , 1978Kousvelari et al 1980;Meurman & Frank, 1991;Featherstone et al 1993). It is also thought to prevent calculus formation on the dental surfaces by controlling the precipitation of calcium phosphate from supersaturated saliva (Hay & Moreno, 1989).…”
mentioning
confidence: 99%
“…In contradication, (15) reported that after free calcium and phosphate were removed from whole saliva by dialysis, the remaining organic molecules imparted the same resistance to demineralization as whole saliva.…”
Section: Discussionmentioning
confidence: 99%